Implementation of skill test (Web based skill assessment system) using Java 2 platform for IKRAM solutions - Imrani, Khurram Junaid (2006)
Skill assessment is essential for organizations to profile candidate’s skills before hiring. There is a need of pre assessment of candidate skills before job interview. Such pre assessment rates candidate’s skill level and makes human resource managers to select the most suitable candidate for their organizations. Such pre assessment should be simple, easy to manage, easy to access and economical. Online pre assessment is the effective way of screening candidates for organization. Skill Test is a web based application for online screening of job candidate. Skill Test is based on the latest platform and technologies. Java was used to implement the Skill Test. Java has become the language of choice for implementing Internet-based applications and software for devices that communicate over a net work. The request-response model of communication was used to design the application. The servlet demonstrates communication between clients and servers. A client sends request to the server. The servlet container receives the request and directs it to be processed by the appropriate servlet. The servlet interacts with a database or other server side components such as other servlets, or JSPs. The servlet returns its results to the client normally in the form of HTML document to display in a browser. Java Server Pages were used to simplify the delivery of dynamic Web content. MySQL database was used to maintain application data. Skill Test gives complete test-customizing features with reliable performance using only a browser. It provides one such solution to conduct pre assessment tests online to get the highly qualified candidates quickly and easily and it saves time and money of the organization.